The Overlap Between Teen Dating Violent Offending and Violent Victimization - Pusch, Natasha (Criminal justice and behavior, 2021)
Teen dating violence (TDV) affects both males and females, and the negative consequences associated with such violence last into adulthood. This study had three objectives: (a) determine the extent of overlap in TDV offending and TDV victimization, (b) test whether social ties explain the TDV overlap, and (c) assess whether the effects of social ties on teen dating violence are invariant between sexes. This study used data from the 2018 Arizona Youth Study (N = 5,189). The findings confirmed that TDV overlap exists. In addition, social ties appeared to partially explain this overlap. Finally, some social ties appeared more general, predicting TDV for both sexes, whereas others were not. For instance, Paternal Attachment was found to reduce the probability of dating violence among female participants only. The findings lend support to prevention programs that aim to strengthen ties between parents and teens.